Heme oxygenase-1 protects tumor cells against photodynamic therapy-mediated cytotoxicity - Nowis, D (2006)
Photodynamic therapy is a promising antitumor treatment modality approved for the management of both early and advanced tumors. The mechanisms of its antitumor action include generation of singlet oxygen and reactive oxygen species that directly damage tumor cells and tumor vasculature. A number of mechanisms seem to be involved in the protective responses to PDT that include activation of transcription factors, heat shock proteins, antioxidant enzymes and antiapoptotic pathways. Elucidation of these mechanisms might result in the design of more effective combination strategies to improve the antitumor efficacy of PDT. Using DNA microarray analysis to identify stress-related genes induced by Photofrin-mediated PDT in colon adenocarcinoma C-26 cells, we observed a marked induction of heme oxygenase-1 (HO-1). Induction of HO-1 with hemin or stable transfection of C-26 with a plasmid vector encoding HO-1 increased resistance of tumor cells to PDT-mediated cytotoxicity. On the other hand, zinc (II) propoporphyrin IX, an HO-1 inhibitor, markedly augmented PDT-mediated cytotoxicity towards C-26 and human ovarian carcinoma MDAH2774 cells. Neither bilirubin, biliverdin nor carbon monoxide, direct products of HO-1 catalysed heme degradation, was responsible for cytoprotection. Importantly, desferrioxamine, a potent iron chelator significantly potentiated cytotoxic effects of PDT. Altogether our results indicate that HO-1 is involved in an important protective mechanism against PDT-mediated phototoxicity and administration of HO-1 inhibitors might be an effective way to potentiate antitumor effectiveness of PDT.